2018
DOI: 10.1007/s13555-018-0261-2
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nail Psoriasis Successfully Treated with Intralesional Methotrexate

Abstract: Psoriasis is a chronic inflammatory disease affecting the skin, nails, and joints. About 61% of psoriatic patients have nail involvement that can cause a significant social problem. Treating nail psoriasis is challenging but can improve the health outcomes and quality of life of patients. Treatment options available for nail psoriasis including topical therapy, intralesional injections, and systemic and biologic agents have various side effects and some benefits. Management is currently inconclusive. Intralesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…19The incorporation of Feraheme particles into a polyurethane may be beneficial for the treatment of this form of psoriasis, and less painful than the injection of methotrexate into nail recently reported as an alternative to systemic use of anti-inflammatory therapies. (20) Our findings suggesting the potential utility for the topical application of Feraheme in psoriasis is in line with the earlier study demonstrating that topical application of Feraheme prevents the formation of bacterial biofilm on teeth and reduces tooth decay. (21) Future research focused on optimizing the Feraheme formulation for topical administration and testing it in other models, more closely resembling human psoriasis (e.g., pigs or genetically engineered mouse models) is needed to verify our findings.…”
Section: Discussionsupporting
confidence: 91%
“…19The incorporation of Feraheme particles into a polyurethane may be beneficial for the treatment of this form of psoriasis, and less painful than the injection of methotrexate into nail recently reported as an alternative to systemic use of anti-inflammatory therapies. (20) Our findings suggesting the potential utility for the topical application of Feraheme in psoriasis is in line with the earlier study demonstrating that topical application of Feraheme prevents the formation of bacterial biofilm on teeth and reduces tooth decay. (21) Future research focused on optimizing the Feraheme formulation for topical administration and testing it in other models, more closely resembling human psoriasis (e.g., pigs or genetically engineered mouse models) is needed to verify our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Mokni and Duarte reported progressive improvement in nail dystrophy with intralesional MTX injection in nail psoriasis [9,10]. Mittal et al reported that intralesional methotrexate and corticosteroid injections show similar efficacy in nail psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate and cyclosporine [ 26 ] are also used systemically in psoriasis treatment. There have been reports of successful treatment of nail psoriasis with intralesional methotrexate [ 28 , 29 , 30 ]. In one study, intramatricial methotrexate administration was found to be more effective in treating nail psoriasis than administration of triamcinolone or cyclosporine, with fewer side effects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%